2013
DOI: 10.3121/cmr.2013.1176.ps2-13
|View full text |Cite
|
Sign up to set email alerts
|

PS2-13: Implementing a Lean Management System in Primary Care: Facilitators and Barriers from the Frontlines

Abstract: 158 HMORN 2013 -Selected Abstracts safety net population. Methods: This randomized controlled trial began in October 2011 among patients of Cambridge Health Alliance (CHA), an urban safety net health care system. We identified patients discharged from the medical service with lengths of stay 3 days or more, admission in the prior 6 months, age 60+ years, or admission for COPD or congestive heart failure. We randomized patients to the PN intervention or usual care alone. In the PN intervention, a bilingual hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…Furthermore, the activities of leading, visioning, and especially empowering were considered essential for successful Lean leadership. Many of the studies (four of nine) referred to the fact that Lean leaders should have the abilities to empower, trust, and engage other team-members (25;29;30;40). In addition, many studies suggested a visible leadership of Lean was a recognizable feature of Lean leadership (29;30;40;41).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the activities of leading, visioning, and especially empowering were considered essential for successful Lean leadership. Many of the studies (four of nine) referred to the fact that Lean leaders should have the abilities to empower, trust, and engage other team-members (25;29;30;40). In addition, many studies suggested a visible leadership of Lean was a recognizable feature of Lean leadership (29;30;40;41).…”
Section: Resultsmentioning
confidence: 99%
“…Data walls collect and display locally relevant data (42). Visually displaying daily progress-technique is known more formally in Lean terminology as the use of a “daily management” or “daily engagement” system (25;29;40). Communication was one of the key factors referred to in most articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations